Diagnostic and therapeutic conduct in iatrogenic wounds - Gateño, Nisso; Torterolo, Edgardo (Cirugía del Uruguay, 2021)
Iatrogenic neck wounds produced during instrumental diagnostic and / or treatment maneuvers are analyzed, excluding those produced during surgical interventions.